Functional Outcome of Unreamed Nailing in Open Shaft of Tibia Fracture - Bhatti, Muhammad Yasir; Shah, Farooq Ahmad; Munawar, Riaz; Mehdi, Arslan Sana (Indus Journal of Bioscience Research, 2025)
Background: The major bone in the lower limb that bears weight is the tibia. Compared to developed countries, tibial fractures are more common in less developed countries due to traffic accidents. Treatment options for tibial fractures include both conservative and surgical methods. Because they improve functional outcome with a lower incidence of malunion, infection, range of motion, and early recovery, reamed and unreamed nailing surgical procedures are becoming increasingly important in the surgical treatment of tibial fractures. Objective: The aim of the present investigation was to ascertain the functional outcome of unreamed nails in patients who presented with open shaft of tibia fractures to Orthopedics Surgery Unit, Ghazi Khan medical college & Allama Iqbal Teaching Hospital Dera Ghazi Khan, Pakistan. Study Design: Descriptive case series. Study Duration: The present research was conducted from 27-7-2024 to 25-2-2025. Material and Methods: The study involved the selection of around 24 patients. After a description of the study’s advantages and dangers, patients were prompted to execute a written informed consent form before they could participate. The performa contained information on their demographic statistics. At each follow-up, patients who had unreamed nailing were assessed, and the functional result was recorded. Results: The respondent’s age ranged from 19 to 55 years old, with a mean age of 33.781. 31.25 percent were women and 68.75 percent were men. The union lasted an average of 14.7188 SD 3.039 weeks, with a minimum of 10 weeks and a maximum of 23 weeks. Sixty-two percent of the union lasted less than 15 weeks, while 37.5% of the union lasted more than 15 weeks. While 18.8% shown poor functional performance, 56.3% demonstrated good outcome, and 25% demonstrated excellent outcome. Conclusion: In the open shaft of the tibia fracture, the study demonstrated an outstanding to good functional result for the unreamed nail. Age, gender, patient BMI, and functional outcome all varied statistically.